SINKRONISASI PERATURAN PERUNDANG-UNDANGAN MENGENAI PERKAWINAN BEDA AGAMA - Zaidah Nur Rosidah (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2013)
This study aims to know the horizontal and vertical synchronization of legislation on interfaith marriage in Indonesia. This study is a part of normative legal research which is projected to examine the harmonization of legislation regarding interfaith marriage. The current approach of this research is legislation approach (statue approach) in which the data was collected by reciting the literature of primary and secondary legal materials. The next to analysis the data, the researcher examined them through horizontal and vertical synchronization. And the last, the finding outs are : the first, it horizontally occurs discrepancies between the regulation No. 1 of 1974 on Marriage and the regulation No. 23 of 2006 on Demographic and Civic Administration. According to the marriage regulation, interfaith marriage is prohibited meanwhile Demographic and Civic Administration regulation allows it. The second, vertically, between the Marriage regulation of the Government Regulation No. 9 of 1975 and Presidential Decree No. 9 of 1991 already contained synchronization that prohibits interfaith marriage. However, the Cross Marriage Regulation No. 158 of 1898 occurred discrepancies in where Marriage regulation prohibits people to do the interfaith marriage, meanwhile according to the Cross Marriage Regulation, interfaith is not a barrier to marry.